Biotechnological solutions for major cotton (Gossypium hirsutum) pathogens and pests. (2019) - Tarazi, Roberto; Jimenez, Jose Leonardo Santos; Vaslin, Maite F.S.
Abstract: Cotton ( Gossypium spp. L.) is the largest source of natural fibers in the world, with a planted area of more than 33 million hectares in 2019. Biotic stress caused by a variety of pathogens and pests has considerable negative impacts on cotton, and control measures increase global production costs. Among the most important diseases affecting cotton are bacteria and fungi that infect leaves, stems, roots and fruits. In addition, viruses, nematodes, insects and mites cause considerable losses. Here, we summarize the diversity of biotic stresses affecting the cotton crop and highlight present and future biotechnological solutions for disease control, including transgenes, RNAi, gene editing and bioagents. We demonstrate that "Ag Biotech" solutions help keep the cotton industry sustainable in cotton-producing countries.